SHOULD MONETARY STATEMENTS SHOW 'MONETARY' OR 'ECONOMIC' INCOME? - Hylton, Delmer P. (The Accounting Review, 1951)
Abstract This article deals with conventional approach in the preparation of financial statements. The adoption of last in first out (LIFO) inventory methods and is now widely urging that the cost of fixed assets be abandoned as the basis for the computation of the allowable depreciation charge. Both of these innovations have been defended with the assertion that the conventional methods show "dollar" income, but that such income is misleading, and that the adoption of some other method will tend to show "economic" or "true" income. It might be well to inquire into the trend as now evidenced and into the desirability of that trend. Thus until all business transactions are by some means converted from the basis of monetary units to purchasing-power or some other method of reporting "economic income," it seems that accounting statements will best serve their purpose by adhering to the usual and accepted standard of measure, the dollar. This would involve the repudiation of the LIFO inventory method in order that all accounts would then reflect monetary income on an objective basis.